Prognostic correlates of combined coronary flow reserve assessment on left anterior descending and right coronary artery in patients with negative stress echocardiography by wall motion criteria. Issue 17 (3rd May 2009) - Cortigiani, L; Rigo, F; Sicari, R; Gherardi, S; Bovenzi, F; Picano, E
Abstract : Aims: To assess the prognostic correlates of Doppler echocardiographically derived coronary flow reserve (CFR) on two coronaries in patients with negative stress echo. Vasodilator stress echocardiography allows dual imaging of regional wall motion and CFR both on left anterior descending (LAD) and right coronary artery (RCA). Methods: The study group comprised 460 patients with known or suspected coronary artery disease and negative stress echo by wall motion criteria. All underwent dipyridamole (up to 0.84 mg/kg over 6 minutes) stress echo with CFR evaluation of either LAD or RCA by Doppler, and were followed up for a median of 32 months. A CFR value of ⩽2.0 was taken as abnormal. Results: CFR was abnormal in 174 patients (38%) (57 in LAD only, 48 in RCA only, and 69 in both LAD and RCA) and normal in 286 patients (62%). During follow-up, there were 77 cardiac events: 5 deaths, 44 acute coronary syndromes (6 STEMI, and 38 NSTEMI) and 28 late (>6 months from stress echo) revascularisations. CFR of ⩽2.0 on LAD was the strongest multivariable predictor of either definite (death, acute coronary syndrome) and major (death, acute coronary syndrome, late revascularisation) events, followed by diabetes mellitus. Anti-ischaemic therapy at the time of testing and resting wall motion abnormality were also independently associated with major events. Preserved CFR in both LAD and RCA was associated with better (p<0.0001) definite and major event-free survival compared to abnormal CFR in one or both coronary vessels. Conclusion: CFR evaluation of either LAD or RCA allows the identification of distinct prognostic patterns. In particular, preserved CFR in both coronary vessels is highly predictive of a very favourable outcome, while reduced CFR in either coronary vessel, and especially on LAD, is a strong predictor of future cardiac events.